Pengertian, Sejarah dan Gagasan Dasar Multikulturalisme - Novianti Hardini; Rizqan Fadhli; Jessica Tri Agustin (Hidayah : Cendekia Pendidikan Islam dan Hukum Syariah, 2025)
Multiculturalism is a view that recognizes and respects cultural diversity in social life, politics, and community values. This concept emphasizes the importance of recognizing differences in cultural identity as the basis for creating a harmonious, peaceful, and inclusive society. Historically, the idea of ​​multiculturalism emerged as a response to the melting pot paradigm in countries with high immigration rates, which tend to assimilate minority cultures into the dominant culture. Conversely, multiculturalism seeks to maintain the cultural identity of each group while building social cohesion within the framework of shared life. This study uses a qualitative descriptive method with a literature study approach to examine the definition, history, and basic ideas of multiculturalism from various literature sources. The results of the study show that multiculturalism has a strong foundation in the principles of respect, tolerance, equal rights, and social justice in a pluralistic society. A deep understanding of this concept is very important in the context of a complex and diverse modern society, because it is able to strengthen mutual respect, build social solidarity, and maintain national unity amidst cultural, religious, and ethnic differences. Thus, multiculturalism is not only a social concept but also a cultural strategy for realizing a just and harmonious life together.